Loading web-font TeX/Math/Italic

The Stacks project

10.115 Noether normalization

In this section we prove variants of the Noether normalization lemma. The key ingredient we will use is contained in the following two lemmas.

Lemma 10.115.1. Let n \in \mathbf{N}. Let N be a finite nonempty set of multi-indices \nu = (\nu _1, \ldots , \nu _ n). Given e = (e_1, \ldots , e_ n) we set e \cdot \nu = \sum e_ i\nu _ i. Then for e_1 \gg e_2 \gg \ldots \gg e_{n-1} \gg e_ n we have: If \nu , \nu ' \in N then

(e \cdot \nu = e \cdot \nu ') \Leftrightarrow (\nu = \nu ')

Proof. Say N = \{ \nu _ j\} with \nu _ j = (\nu _{j1}, \ldots , \nu _{jn}). Let A_ i = \max _ j \nu _{ji} - \min _ j \nu _{ji}. If for each i we have e_{i - 1} > A_ ie_ i + A_{i + 1}e_{i + 1} + \ldots + A_ ne_ n then the lemma holds. For suppose that e \cdot (\nu - \nu ') = 0. Then for n \ge 2,

e_1(\nu _1 - \nu '_1) = \sum \nolimits _{i = 2}^ n e_ i(\nu '_ i - \nu _ i).

We may assume that (\nu _1 - \nu '_1) \ge 0. If (\nu _1 - \nu '_1) > 0, then

e_1(\nu _1 - \nu '_1) \ge e_1 > A_2e_2 + \ldots + A_ ne_ n \ge \sum \nolimits _{i = 2}^ n e_ i|\nu '_ i - \nu _ i| \ge \sum \nolimits _{i = 2}^ n e_ i(\nu '_ i - \nu _ i).

This contradiction implies that \nu '_1 = \nu _1. By induction, \nu '_ i = \nu _ i for 2 \le i \le n. \square

Lemma 10.115.2. Let R be a ring. Let g \in R[x_1, \ldots , x_ n] be an element which is nonconstant, i.e., g \not\in R. For e_1 \gg e_2 \gg \ldots \gg e_{n-1} \gg e_ n = 1 the polynomial

g(x_1 + x_ n^{e_1}, x_2 + x_ n^{e_2}, \ldots , x_{n - 1} + x_ n^{e_{n - 1}}, x_ n) = ax_ n^ d + \text{lower order terms in }x_ n

where d > 0 and a \in R is one of the nonzero coefficients of g.

Proof. Write g = \sum _{\nu \in N} a_\nu x^\nu with a_\nu \in R not zero. Here N is a finite set of multi-indices as in Lemma 10.115.1 and x^\nu = x_1^{\nu _1} \ldots x_ n^{\nu _ n}. Note that the leading term in

(x_1 + x_ n^{e_1})^{\nu _1} \ldots (x_{n-1} + x_ n^{e_{n-1}})^{\nu _{n-1}} x_ n^{\nu _ n} \quad \text{is}\quad x_ n^{e_1\nu _1 + \ldots + e_{n-1}\nu _{n-1} + \nu _ n}.

Hence the lemma follows from Lemma 10.115.1 which guarantees that there is exactly one nonzero term a_\nu x^\nu of g which gives rise to the leading term of g(x_1 + x_ n^{e_1}, x_2 + x_ n^{e_2}, \ldots , x_{n - 1} + x_ n^{e_{n - 1}}, x_ n), i.e., a = a_\nu for the unique \nu \in N such that e \cdot \nu is maximal. \square

Lemma 10.115.3. Let k be a field. Let S = k[x_1, \ldots , x_ n]/I for some proper ideal I. If I \not= 0, then there exist y_1, \ldots , y_{n-1} \in k[x_1, \ldots , x_ n] such that S is finite over k[y_1, \ldots , y_{n-1}]. Moreover we may choose y_ i to be in the \mathbf{Z}-subalgebra of k[x_1, \ldots , x_ n] generated by x_1, \ldots , x_ n.

Proof. Pick f \in I, f\not= 0. It suffices to show the lemma for k[x_1, \ldots , x_ n]/(f) since S is a quotient of that ring. We will take y_ i = x_ i - x_ n^{e_ i}, i = 1, \ldots , n-1 for suitable integers e_ i. When does this work? It suffices to show that \overline{x_ n} \in k[x_1, \ldots , x_ n]/(f) is integral over the ring k[y_1, \ldots , y_{n-1}]. The equation for \overline{x_ n} over this ring is

f(y_1 + x_ n^{e_1}, \ldots , y_{n-1} + x_ n^{e_{n-1}}, x_ n) = 0.

Hence we are done if we can show there exists integers e_ i such that the leading coefficient with respect to x_ n of the equation above is a nonzero element of k. This can be achieved for example by choosing e_1 \gg e_2 \gg \ldots \gg e_{n-1}, see Lemma 10.115.2. \square

Lemma 10.115.4.slogan Let k be a field. Let S = k[x_1, \ldots , x_ n]/I for some ideal I. If I \neq (1), there exist r\geq 0, and y_1, \ldots , y_ r \in k[x_1, \ldots , x_ n] such that (a) the map k[y_1, \ldots , y_ r] \to S is injective, and (b) the map k[y_1, \ldots , y_ r] \to S is finite. In this case the integer r is the dimension of S. Moreover we may choose y_ i to be in the \mathbf{Z}-subalgebra of k[x_1, \ldots , x_ n] generated by x_1, \ldots , x_ n.

Proof. By induction on n, with n = 0 being trivial. If I = 0, then take r = n and y_ i = x_ i. If I \not= 0, then choose y_1, \ldots , y_{n-1} as in Lemma 10.115.3. Let S' \subset S be the subring generated by the images of the y_ i. By induction we can choose r and z_1, \ldots , z_ r \in k[y_1, \ldots , y_{n-1}] such that (a), (b) hold for k[z_1, \ldots , z_ r] \to S'. Since S' \to S is injective and finite we see (a), (b) hold for k[z_1, \ldots , z_ r] \to S. The last assertion follows from Lemma 10.112.4. \square

Lemma 10.115.5. Let k be a field. Let S be a finite type k algebra and denote X = \mathop{\mathrm{Spec}}(S). Let \mathfrak q be a prime of S, and let x \in X be the corresponding point. There exists a g \in S, g \not\in \mathfrak q such that \dim (S_ g) = \dim _ x(X) =: d and such that there exists a finite injective map k[y_1, \ldots , y_ d] \to S_ g.

Proof. Note that by definition \dim _ x(X) is the minimum of the dimensions of S_ g for g \in S, g \not\in \mathfrak q, i.e., the minimum is attained. Thus the lemma follows from Lemma 10.115.4. \square

Lemma 10.115.6. Let k be a field. Let \mathfrak q \subset k[x_1, \ldots , x_ n] be a prime ideal. Set r = \text{trdeg}_ k\ \kappa (\mathfrak q). Then there exists a finite ring map \varphi : k[y_1, \ldots , y_ n] \to k[x_1, \ldots , x_ n] such that \varphi ^{-1}(\mathfrak q) = (y_{r + 1}, \ldots , y_ n).

Proof. By induction on n. The case n = 0 is clear. Assume n > 0. If r = n, then \mathfrak q = (0) and the result is clear. Choose a nonzero f \in \mathfrak q. Of course f is nonconstant. After applying an automorphism of the form

k[x_1, \ldots , x_ n] \longrightarrow k[x_1, \ldots , x_ n], \quad x_ n \mapsto x_ n, \quad x_ i \mapsto x_ i + x_ n^{e_ i}\ (i < n)

we may assume that f is monic in x_ n over k[x_1, \ldots , x_ n], see Lemma 10.115.2. Hence the ring map

k[y_1, \ldots , y_ n] \longrightarrow k[x_1, \ldots , x_ n], \quad y_ n \mapsto f, \quad y_ i \mapsto x_ i\ (i < n)

is finite. Moreover y_ n \in \mathfrak q \cap k[y_1, \ldots , y_ n] by construction. Thus \mathfrak q \cap k[y_1, \ldots , y_ n] = \mathfrak pk[y_1, \ldots , y_ n] + (y_ n) where \mathfrak p \subset k[y_1, \ldots , y_{n - 1}] is a prime ideal. Note that \kappa (\mathfrak p) \subset \kappa (\mathfrak q) is finite, and hence r = \text{trdeg}_ k\ \kappa (\mathfrak p). Apply the induction hypothesis to the pair (k[y_1, \ldots , y_{n - 1}], \mathfrak p) and we obtain a finite ring map k[z_1, \ldots , z_{n - 1}] \to k[y_1, \ldots , y_{n - 1}] such that \mathfrak p \cap k[z_1, \ldots , z_{n - 1}] = (z_{r + 1}, \ldots , z_{n - 1}). We extend the ring map k[z_1, \ldots , z_{n - 1}] \to k[y_1, \ldots , y_{n - 1}] to a ring map k[z_1, \ldots , z_ n] \to k[y_1, \ldots , y_ n] by mapping z_ n to y_ n. The composition of the ring maps

k[z_1, \ldots , z_ n] \to k[y_1, \ldots , y_ n] \to k[x_1, \ldots , x_ n]

solves the problem. \square

Lemma 10.115.7. Let R \to S be an injective finite type ring map. Assume R is a domain. Then there exists an integer d and a factorization

R \to R[y_1, \ldots , y_ d] \to S' \to S

by injective maps such that S' is finite over R[y_1, \ldots , y_ d] and such that S'_ f \cong S_ f for some nonzero f \in R.

Proof. Pick x_1, \ldots , x_ n \in S which generate S over R. Let K be the fraction field of R and S_ K = S \otimes _ R K. By Lemma 10.115.4 we can find y_1, \ldots , y_ d \in S such that K[y_1, \ldots , y_ d] \to S_ K is a finite injective map. Note that y_ i \in S because we may pick the y_ j in the \mathbf{Z}-algebra generated by x_1, \ldots , x_ n. As a finite ring map is integral (see Lemma 10.36.3) we can find monic P_ i \in K[y_1, \ldots , y_ d][T] such that P_ i(x_ i) = 0 in S_ K. Let f \in R be a nonzero element such that fP_ i \in R[y_1, \ldots , y_ d][T] for all i. Then fP_ i(x_ i) maps to zero in S_ K. Hence after replacing f by another nonzero element of R we may also assume fP_ i(x_ i) is zero in S. Set x_ i' = fx_ i and let S' \subset S be the R-subalgebra generated by y_1, \ldots , y_ d and x'_1, \ldots , x'_ n. Note that x'_ i is integral over R[y_1, \ldots , y_ d] as we have Q_ i(x_ i') = 0 where Q_ i = f^{\deg _ T(P_ i)}P_ i(T/f) which is a monic polynomial in T with coefficients in R[y_1, \ldots , y_ d] by our choice of f. Hence R[y_1, \ldots , y_ d] \subset S' is finite by Lemma 10.36.5. Since S' \subset S we have S'_ f \subset S_ f (localization is exact). On the other hand, the elements x_ i = x'_ i/f in S'_ f generate S_ f over R_ f and hence S'_ f \to S_ f is surjective. Whence S'_ f \cong S_ f and we win. \square


Comments (2)

Comment #5420 by Brian Shih on

What does the notation >> mean?

Comment #5647 by on

If we say then that translates into " is much larger than " in the English language. Does that help?


Your email address will not be published. Required fields are marked.

In your comment you can use Markdown and LaTeX style mathematics (enclose it like $\pi$). A preview option is available if you wish to see how it works out (just click on the eye in the toolbar).

Unfortunately JavaScript is disabled in your browser, so the comment preview function will not work.

All contributions are licensed under the GNU Free Documentation License.